Assessment of the impacts of the desertification process in the Western Seridó by biophysical and social indicators (Research, Society and Development, 2022)
The process of degradation of semi-arid lands is associated with environmental and economic vulnerabilities related to factors of natural and mainly anthropic origin. Historically, the micro-region of Seridó Ocidental Paraibano had the Caatinga as a means of subsistence and source of income. The abusive removal of vegetation cover is linked to the presence of exploratory economic activities, such as agriculture, livestock, cotton farming and since then mining. Studies initiated in the 1980s by Vasconcelos Sobrinho already pointed to the micro-region as an area of ​​high risk of desertification, later called the Desertification Nucleus due to the natural characteristics and consequences of human activities that devastate large spaces for pasture, removing firewood and charcoal to consumption, as well as for potteries, bakeries and other energy-saving purposes. This work surveys the natural characteristics (rainfall, climate, soil and relief, as well as the removal of firewood and wood for local supply and other locations) that favor environmental degradation and the processes that lead to desertification.